PEMANFAATAN BUNGA TELANG SEBAGAI UPAYA PENINGKATAN PENDAPATAN DI GAMPONG BAROH BLANG RIMUENG, SYAMTALIRA BAYU, ACEH UTARA - maryana, maryana (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2024)
In an effort to increase income, particularly in the food sector, there is a program of planting and utilizing herbs. One of the herbs that people are starting to pay attention to is the butterfly pea (Clitoria ternatea), which is famous for its bright blue flowers and can be consumed. This flower is suitable to be processed into a health drink because it does not have an odor so it doesn't interfere when used as a mixture. In addition, a mixture of butterfly pea in drinks can also enhance the appearance because of the varied colors. Butterfly pea is a type of plant that can be found in residents' yards which is usually used as a cultivated plant. In the village of Baroh Blang Rimueng, Syamtalira Bayu sub-district, North Aceh Regency, there are several residents who cultivate butterfly pea in their yards, but many of them do not understand the benefits contained in butterfly pea. The target of this community service program are residents and PKK mothers, so that the community gets knowledge about processing products with the main ingredient of butterfly pea which can provide additional income for housewives.